A Semi-Automatic Framework for Practical Transcription of Foreign Person Names in Lithuanian - Gailius Raškinis; Darius Amilevičius; Danguolė Kalinauskaitė; Artūras Mickus; Daiva Vitkutė-Adžgauskienė; Antanas Čenys; Tomas Krilavičius (Mathematics, 2025)
We present a semi-automatic framework for transcribing foreign personal names into Lithuanian, aimed at reducing pronunciation errors in text-to-speech systems. Focusing on noisy, web-crawled data, the pipeline combines rule-based filtering, morphological normalization, and manual stress annotation—the only non-automated step—to generate training data for character-level transcription models. We evaluate three approaches: a weighted finite-state transducer (WFST), an LSTM-based sequence-to-sequence model with attention, and a Transformer model optimized for character transduction. Results show that word-pair models outperform single-word models, with the Transformer achieving the best performance (19.04% WER) on a cleaned and augmented dataset. Data augmentation via word order reversal proved effective, while combining single-word and word-pair training offered limited gains. Despite filtering, residual noise persists, with 54% of outputs showing some error, though only 11% were perceptually significant.